Bisphenol A exposure alters hormonal modulation and responsivity in the prostate of aged female gerbils - Ferrato, Luara Jesus [UNESP]; Ruiz, Thalles Fernando Rocha [UNESP]; de Souza, Lorena Gabriela [UNESP]; Brito-Filho, Gervásio Evangelista [UNESP]; Colleta, Simone Jacovaci [UNESP]; Leonel, Ellen Cristina Rivas; Taboga, Sebastião Roberto [UNESP] (Elsevier, 2025)
The female prostate is a gland regulated by steroid hormones for homeostasis. Bisphenol A (BPA) is an endocrine disruptor related to the progression of malignant lesions in prostate. The aim of this study was to analyze the hormonal modulation and responsiveness of the prostate of aged female gerbils previously exposed to BPA. Females were exposed to 50 μg/kg/day during pregnancy and lactation, and the prostate was analyzed at 18 months of age. Control groups were included to normalize the analysis. The samples were analyzed using histological and immunohistochemical techniques for the expression of androgen (AR), estrogen (ERα and ERβ), prolactin (PRL), and progesterone (PR) receptors, as well as steroidogenic enzymes (5α-reductase and aromatase) and the proliferation (PHH3) and epigenetic (EZH2) markers. Protein quantification was also performed for the receptors and enzymes described, as well as morphological and morphometric analyses of the gland. The results showed an increase in the epithelial expression of AR and ERα and a decrease in the expression of ERβ in this compartment. In addition, a decrease in epithelial expression was observed for the 5α-reductase and aromatase in the prostate epithelium and an increase in the expression of PHH3 and EZH2. By Western blot analyses, significant differences were observed in the protein quantification of the receptors and enzymes described. Thus, the current study showed the role of BPA in intraprostatic hormonal modulation, through alterations in the expression of hormone receptors and the conversion of enzymes in the female prostate, which can lead to the progression of malignant lesions in this tissue.
Keywords: Bisphenol A; Enzymes; Female prostate; Hormone receptors; Lesions